Consumption and cost trends of EGFR TKIs: influences of reimbursement and national price negotiation - Di Wu; Jianxiang Xie; Huizhen Dai; Wentong Fang (BMC, 2022)
Abstract Background Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) have been widely used in the treatment of EGFR mutation non-small-cell lung cancer. The Chinese government has made great efforts to improve the availability and affordability of these drugs. The aim of this study was to investigate the trends in the consumption and cost of EGFR TKIs in Nanjing, a developed city in China, and evaluate the influence of health insurance coverage and national price negotiation on drug consumption. Methods Data about EGFR TKIs applications in 2010-2019 were extracted from Jiangsu Medicine Information Institute. Five types of EGFR TKIs were included. Consumption was expressed in defined daily doses (DDDs) and expenditure. The correlation between defined daily cost (DDC) and DDDs was analyzed by Pearson's correlation test. Results The DDC, number of DDDs and expenditure of EGFR TKIs changed little from 2010 to 2015. National price negotiation was initiated as a policy and low-price generic gefitinib came into the market in 2016. Three types of EGFR TKIs moved into the coverage of the national health insurance since 2017. Hence, the DDC decreased, and the number of DDDs increased significantly year by year since 2016. The first generation TKIs always made up of comprised the majority of the total consumption. The predominantly prescribed TKIs were gefitinib and icotinib. DDC was negatively correlated with the number of DDDs. The number of DDDs increased significantly after health insurance enrollment, price negotiation and generic drug replacement. Conclusion The consumption of EGFT TKIs has increased and the DDC of EGFR TKIs has decreased since 2016. These trends may be attributed to drug reimbursement, price negotiation and generic drug replacement. Further efforts are needed to translate the high consumption of EGFR TKIs into clinical benefits.